Bibliometric study on the variables solar energy, economy, Brazil - Ítalo Freire, Anderson; Fontgalland, Isabel (Latin American Journal of Energy Research, 2023)
This bibliometric study traces and refines the condition of publications related to Solar Energy, Economy,and Brazil as joint terms in the same publication, varying from the year 2010 to the year 2020,considering the appearance of the term in topics, titles, or abstracts, identifying the number of thesepublications, their respective authors, in addition to the most cited documents and the most usedkeywords in scientific articles. Bibliometric studies are tools that greatly help the analysis of scientificproduction in each area, and it is no different in topics related to the economy and the electricity sector, asector that has grown in recent years here in Brazil and in the world. Having this initial aspect as a basisfor justification and noting that this growth tends to encourage publications within the area underanalysis, this article is divided into 4 parts, the first and second relating to the introductory part and themethodology used in the investigation, and the last two parts related to what was essentially analyzedwithin the scope of the work and the conclusion on how these publications were stand out in academiaand how production in the area can be improved based on this investigation.